The fission yeast Pvg1p has galactose‐specific pyruvyltransferase activity. Issue 7 (16th February 2013) - Yoritsune, Ken-ichi; Matsuzawa, Tomohiko; Ohashi, Takao; Takegawa, Kaoru
Abstract : N ‐Glycan from the fission yeast Schizosaccharomyces pombe contains outer‐chain pyruvic acid 4, 6‐ketal‐linked galactose (PvGal). Here, we characterized a putative S. pombe pyruvyltransferase, Pvg1p, reported to be essential for biosynthesis of PvGal. When p ‐nitrophenyl‐β‐Gal ( p NP‐β‐Gal) was used as a substrate, the structure of the recombinant Pvg1p product was determined to be p NP‐PvGal by one‐ and two‐dimensional NMR spectroscopy. The recombinant Pvg1p transferred pyruvyl residues from phosphoenolpyruvate specifically to β‐linked galactose. Abstract : ► N ‐Glycan from fission yeast contains pyruvic acid 4, 6‐ketal‐linked galactose. ► Putative Schizosaccharomyces pombe pyruvyltransferase Pvg1p produced in Escherichia coli is characterized. ► Pvg1p transfers pyruvyl residues specifically to β‐linked galactose.